Design of an Electronic Medical Record (EMR) Information ‎System for Vertigo Patients Using Python Algorithms - Ermayanti Astuti; Nita Syahputri; Suryani; Marlina Elfa Lubis; Yahya Tanjung; Indah Lestari (Yayasan Darussalam Bengkulu, 2026)
Technology adaption for healthcare services generally involves the implementation of electronic medical records. Management ini pharmaceutical facilities using Phyton can be achieved by building a CLI (Command Line Interface) or GUI-based data management systems. This system tracks patient history, diagnoses, medication lists, and dosage analysis for vertigo. One subsystem of a healthcare facility’s information system is the electronic medical record. This subsystem is connected to other subsystems within the healthcare facility. With the issuance of Minister of Health Regulation No. 24 of 2022 concering Medical Records, a medical records is defined as a document containing patient identity data, examinations, treatments, procedures, and other services provided to patients. This regulation replaces Ministers of Health Regulation No. 269 of 2008 concerning Medical Records. MENKES Regulation No. Law No. 24 of 2022 explains the purpose of electronics medical records : to improve the quality of healthcare services, provide legal certainty in the implementation and management of medical records, ensure the security, confidentiality, integrity, and availability of medical record data, and realize the implementation and management of digitally-based and integrated medical records. Under these conditions, the Minister of Health stipulates that service facilities are required to implement electronics medical records in their healthcare services. According to Rano Indriadi, an intellectual, an Electronic Medical Record (EMR) is defined as a medical record stored electronically, containing personal data, demographic data, clinical/medical data, and various clinicals events from the beginning of the service process to the end froam various data sources. It actively functions to support medical decision-making